(untitled) (Research, Society and Development, 2021)
The objective of this study was to analyze the current situation of the ICMS-E in the Brazilian states and to estimate the consequences of its non-applicability in the state of Paraíba. Through documentary and bibliographic research, the legal provisions that institute and regulate the ICMS-E in Brazilian states were raised, such as the criteria for redistribution and their respective percentage of participation. The population criterion was used to estimate the value of ICMS-E not passed on to the municipalities of Paraíba, since the legal criteria were not regulated due to the unconstitutionality of the state law. The estimated population of the 5 most populous municipalities in the state and the 5 municipalities with the smallest population were collected, to verify the impact of the non-applicability of the ICMS-E in both realities. In the data analysis, the Population Proportion method was used, where the relative frequency with which this category is observed in the population (p) was calculated according to Mann (2005). The results showed that 17 Brazilian states instituted the ICMS-E under various criteria for the redistribution of resources, among which environmental conservation units, public water sources and solid waste treatment stand out. In Paraíba, the losses related to the non-applicability of the ICMS-E in the analyzed period add up to approximately 845 million reais. Thus, the poorest 5 municipalities stopped receiving an average of 430 thousand reais / year. It is concluded, therefore, that the ICMS-E is an important tax mechanism for environmental management capable of stimulating the conservation of the environment.